The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1516-635x1704531-536
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Bioaccumulation in Eggs of Hens Experimentally Intoxicated with Methylmercury Chloride and Detoxified with a Humic-Aluminosilicate Preparation

Abstract: Eggs; humic-aluminosilicate preparation; mercury.Submitted: July/2014 Approved: March/2015 ABSTRACTThe aim of the study was to evaluate the effectiveness of preventivedetox preparation (P-dP) based on humic and aluminosilicate substances in the diet of laying hens (3% daily dose) previously intoxicated with methylmercury chloride (CH 3 ClHg, 5 mg Hg/kg feed mixture) for six weeks. Mercury content in the whole eggs of the group intoxicated with CH 3 ClHg increased compared to the control group: 488-fold after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…For example, an average of 7.06 mg·kg -1 of mercury was found in drinking water at a broiler farm in Saudi Arabia, which resulted in increased Hg concentration in liver samples of chickens up to a level of 1,167 µg·kg -1 [46]. Mercury also easily accumulates in egg content, liver, and muscles when methylmercury is presented in the feed [26]. This can be prevented to a limited extent when feed additives containing humic compounds and aluminosilicates are supplemented [26,47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, an average of 7.06 mg·kg -1 of mercury was found in drinking water at a broiler farm in Saudi Arabia, which resulted in increased Hg concentration in liver samples of chickens up to a level of 1,167 µg·kg -1 [46]. Mercury also easily accumulates in egg content, liver, and muscles when methylmercury is presented in the feed [26]. This can be prevented to a limited extent when feed additives containing humic compounds and aluminosilicates are supplemented [26,47].…”
Section: Resultsmentioning
confidence: 99%
“…Mercury also easily accumulates in egg content, liver, and muscles when methylmercury is presented in the feed [26]. This can be prevented to a limited extent when feed additives containing humic compounds and aluminosilicates are supplemented [26,47]. Another solution is selenium supplementation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Problematyka jest skomplikowana, np. tolerancja zwierząt jest bardzo zróżnicowana (w zależności od gatunku i wieku zwierząt), ponadto zachodzą różne interakcje (synergizm, antagonizm) na poziomie metabolicznym, w związku z czym różna jest biokumulacja tych związków w produktach pochodzenia zwierzęcego (mleko, mięso, jaja, wełna, miód) 2,[29][30][31][32][33] .…”
Section: Wykorzystanie Analityki W Monitoringuunclassified
“…Several studies have shown that feed contaminated with toxic elements, such as arsenic, cadmium, mercury, and lead can determine the bioaccumulation in chicken tissues and eggs [3,4,[14][15][16][17]. As an example, a high content of lead has been detected in chickens' muscle, liver, kidneys, and eggs, particularly in industrialized regions [18], posing a potential threat to public health. Chickens are exposed to lead, mainly from contaminated soil, through various behaviours such as foraging, roosting, grooming, fighting, and dust bathing, as well as their diet.…”
Section: Introductionmentioning
confidence: 99%